2008
DOI: 10.1007/s10350-008-9347-8
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Mucosa-Associated Microflora in Ulcerative Colitis Patients Before and After Restorative Proctocolectomy with an Ileoanal Pouch

Abstract: No bacterium was identified that could be exclusively responsible for the maintenance of the inflammatory process. The mucosa-associated microflora of patients with ulcerative colitis underwent significant changes after proctocolectomy with ileal pouch construction and returned to almost normal values for some bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…The microbiota close to the mucosa, which differs from the luminal microbiota, has so far received less attention, and yet the mucosa-associated microbiota is very close to the inflammatory process. As inflammatory bowel disease (IBD) is a disorder of mucosal inflammation, the mucosa-associated microflora seems to be of great relevance to the disease process (1,20). Differences have been observed between the dominant fecal microbiota and the mucosa-associated microbiota at different sites of the colon and rectum in IBD versus healthy subjects (7).…”
mentioning
confidence: 99%
“…The microbiota close to the mucosa, which differs from the luminal microbiota, has so far received less attention, and yet the mucosa-associated microbiota is very close to the inflammatory process. As inflammatory bowel disease (IBD) is a disorder of mucosal inflammation, the mucosa-associated microflora seems to be of great relevance to the disease process (1,20). Differences have been observed between the dominant fecal microbiota and the mucosa-associated microbiota at different sites of the colon and rectum in IBD versus healthy subjects (7).…”
mentioning
confidence: 99%
“…patients were free to leave the study at any time (withdrawal of consent). other reasons for withdrawal from the investigation were: lack of adherence to the therapeutic schedule or programmed controls (< 85%, poor compliance); onset of symptoms of relapse, confirmed by instrumental procedures (therapeutic failure); onset of drug-related adverse events requiring 1.5±0.6 1.3±0.5 ns t 3 1.4±0.6 1.2±0.4 ns t 4 1.5±0.6 1.2±0.4 P = 0.0040 interruption of treatment. The study was approved by the local ethics committee and all participants subscribed to an informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Whether these abnormalities are the cause or the result of the intense systemic inflammatory response in Uc is still unresolved. However, it is well documented that bacterial microflora is altered in patients with active disease 4 . recent studies reported a great variation in the effects of microbiota, focusing, in particular, on the effects of a pro-inflammatory enterotype on mucosal layer and disease activity 5 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Finally, the ileal mucosa can potentially be changed by the altered physiology ensuing from its new function as a fecal reservoir. 12,13 CD10 is a membrane-associated neutral peptidase, also known as neprilysin, enkephalinase, common acute lymphoblastic leukemia antigen, and neutral endopeptidase. 14 Previous studies have demonstrated its presence on the brush border of small intestinal mucosa and it has been studied and utilized in the diagnosis of microvillous inclusion disease.…”
mentioning
confidence: 99%